Constitutive behaviour of masonry prisms using a full-field measurement technique. (December 2022) - Bello, Ismail; Wardeh, George; González-Fonteboa, Belén; Martínez-Abella, Fernando; Ghorbel, Elhem
Abstract: To obtain analytical models for the compressive behaviour of masonry structures, it is crucial to accurately measure the compressive strengths of its constituents, i.e., brick and mortar. The mechanical properties and the stress-strain relationship under uniaxial compression are essential for thoroughly investigating and evaluating masonry structures. The present work aims to validate a non-contact measuring technique for obtaining full-scale strain and failure patterns and investigate joint mortar composition's effect on masonry behaviour. Forty masonry prisms were manufactured in this study using two distinct types of brick and five different types of mortar varying according to cement and lime contents. The results showed that 2D Digital Image Correlation (DIC) could generate full-strain assessments of masonry prisms, resulting in a full-scale stress-strain analysis. It was also found that, in the post-peak region, prisms with lower cement content exhibit a more ductile behaviour with strain localisation at the joint mortar level. Based on current experimental results and data from the literature, new analytical relationships were presented to predict masonry mechanical properties and masonry complete stress-strain compressive behaviour.